2018
DOI: 10.5194/isprs-archives-xlii-4-w8-85-2018
|View full text |Cite
|
Sign up to set email alerts
|

Spatial Statistical Analyses to Assess the Spatial Extent and Concentration of Multidimensional Poverty in Gauteng Using the South African Multidimensional Poverty Index

Abstract: <p><strong>Abstract.</strong> Assessment of poverty has generally been carried out using “money-metric” measures. But since poverty is multidimensional, these measures fall short of generating a comprehensive picture of the poor. Contrastingly, multidimensional poverty analyses are capable of generating parameters that help in providing holistic understanding of poverty in its various forms. This study compares two indexes of multidimensional poverty computed from census data collected in 200… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…Hence, the application of LISA enables the diagnosis of local instability to ascertain any significant global associations [15]. Previous research has shown that this index is very useful in measuring the multidimensional poverty index [16]. The study reported an evaluation of the relationship between the poverty concentration and prosperity in Gauteng between 2001 and 2011.…”
Section: Introductionmentioning
confidence: 99%
“…Hence, the application of LISA enables the diagnosis of local instability to ascertain any significant global associations [15]. Previous research has shown that this index is very useful in measuring the multidimensional poverty index [16]. The study reported an evaluation of the relationship between the poverty concentration and prosperity in Gauteng between 2001 and 2011.…”
Section: Introductionmentioning
confidence: 99%